2011
DOI: 10.1111/j.1551-2916.2011.04724.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of the Cement Sheath in Steam Treated Oil Wells

Abstract: The material in this document is covered by the provisions of the Copyright Act, by Canadian laws, policies, regulations and international agreements. Such provisions serve to identify the information source and, in specific instances, to prohibit reproduction of materials without written permission. For more information visit http://laws.justice.gc.ca/en/showtdm/cs/C-42Les renseignements dans ce document sont protégés par la Loi sur le droit d'auteur, par les lois, les politiques et les règlements du Canada e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In addition to CF reinforcement at macroscale or microscale, CNT can even bridge the nano-scaled cracks and transfer load from CF to itself, thus delaying crack generation and propagation. [47,[64][65][66][67][68] In addition, as shown in Figure S7, Supporting Information, the XRD and TG results both revealed that the addition of CF and CF-CNT had no influence on the compositions of SSCCs' hydration products while can promote their hydration degree to some extent as observed by the higher overall TG mass losses than the blank specimen, consistent with previous studies. [26,69] As compared, the CF-CNT performed more positively in the promotion of SSCC's hydration degree over the CF due to the nucleating effect of CNTs, which further elucidates the reinforcing mechanisms of CF-CNTs.…”
Section: Mechanical Properties and Microstructures Of Ssccs With Cf-cntssupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to CF reinforcement at macroscale or microscale, CNT can even bridge the nano-scaled cracks and transfer load from CF to itself, thus delaying crack generation and propagation. [47,[64][65][66][67][68] In addition, as shown in Figure S7, Supporting Information, the XRD and TG results both revealed that the addition of CF and CF-CNT had no influence on the compositions of SSCCs' hydration products while can promote their hydration degree to some extent as observed by the higher overall TG mass losses than the blank specimen, consistent with previous studies. [26,69] As compared, the CF-CNT performed more positively in the promotion of SSCC's hydration degree over the CF due to the nucleating effect of CNTs, which further elucidates the reinforcing mechanisms of CF-CNTs.…”
Section: Mechanical Properties and Microstructures Of Ssccs With Cf-cntssupporting
confidence: 88%
“…In addition to CF reinforcement at macroscale or microscale, CNT can even bridge the nano‐scaled cracks and transfer load from CF to itself, thus delaying crack generation and propagation. [ 47,64–68 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is an essential challenge to make the exceptional properties of CNT exhibited at the nanoscale transferred to the macroscale, the dispersing efficiency and CNT/cement bonding should be intensively explored prior to introducing CNT into cementitious binder. Makar et al [3] tried to develop an ethanol/sonication technique to disperse CNT in cement particles. Mi et al [4] employed surfactant enwrapping process to improve the dispersion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In 1952, the API committee adopted standards for six classes of cements used in oil and gas well cementing operations. The mechanical properties of the cement pastes are highly dependent on the curing conditions, which vary along the wellbore depth and corresponding to the exposure to the formation fluids with different conditions [85][86][87]. It is worth noting that the cement pastes used in the oil and gas industry has very low permeability [88].…”
Section: Api Specification For Oil Well Cementsmentioning
confidence: 99%